Relationship between student satisfaction, expectancy, and student performance in an online learning environment a mediated regression analysis - Morales, Retchell L.; Morales, Ryan C.; Caminong, Joliber M. (2020)
The purpose of this study is to examine the relationship between student satisfaction, expectancy, and student performance within the purview of online learning. Using mediated regression analysis, the researchers processed the responses of 672 students from selected schools in Bulacan province. Positive correlation was established between student performance and expectancy. A weak positive correlation was generated between expectancy and student performance. This implies that online learning environment offers opportunities for learning however, a significant implementation of learning goals should be in place to reinforce how students learn.
Keywords: Student performance; Blended learning; Learning